TINJAUAN YURIDIS KEBIJAKAN PEMERINTAH KABUPATEN JEMBER TERHADAP EKSPLOITASI GUMUK - Isnania Citra Saisabela; Fauziyah Fauziyah (Universitas Islam Darul Ulum, 2017)
In the use of hills in Jember District related land rights, which most hills in Jember District is private property rights and its utilization cannot be contrary with national interests. In the article 6 UUPA :